Transformasi Nilai-nilai Hukum Islam dalam Yurisprudensi Putusan Mahkamah Konstitusi Perspektif Teori Hukum Integratif - Saifullah Saifullah; Abdul Azis; Mustafa Lutfi (Fakultas Syariah, 2020)
Abstract:Research examines the rationale and transformation of the value of Islamic law in the Constitutional Court jurisprudence decision No. 06/PUU-II/2004; 27/PUU-VII/2009 and 138/PUU-VII/2009 in the perspective of Integrative Legal Theory (THI). Normative legal research is used with a legislative and conceptual approach and sources of primary and secondary legal materials. The results of the study are the rationale for decision No: 06/PUU-II/2004 according to QS 2: 185, 286, 4: 58, 135; 5: 6,8,42; 16: 9; 22: 7. No: 27/PUU-VII/2009 according to QS. 2: 185; 5: 6; 22: 78, and No: 138 / PUU-VII / 2009, according to QS 2: 173; 4: 13,58; 5: 3, 8, 42; 6: 119.Transforming the value of Islamic law No. 06/PUU-II/2004, values of justice, human rights, facilities, and humanism. No. 27/PUU-VII/2009, the value of effectiveness, not burdensome, realizing benefits, and No. 138/PUU-VII/2009 the value of creating law, a legal substance, benefit, realizing benefit and justice. Three judicial decisions of the Constitutional Court reviewed from the THI indicator have implemented a system of norms, behavior, and values.Keywords: integrative law; Constitutional Court; jurisprudence.Abstrak: Riset menelaah landasan pemikiran dan transformasi nilai hukum Islam pada yurisprudensi putusan mahkamah konstitusi No.06/PUU-II/2004; 27/PUU-VII/2009 dan 138/PUU-VII/2009 dalam perspektif Teori Hukum Integratif (THI). Penelitian hukum normatif digunakan dengan pendekatan perundangan dan konseptual serta sumber bahan hukum primer dan sekunder. Hasil penelitian adalah landasan pemikiran putusan No: 06/PUU-II/2004, sesuai QS. 2 :185, 286 ; 4 : 58, 135 ; 5 : 6,8,42 ; 16 : 9 ; 22 : 7. No: 27/PUU-VII/2009, sesuai QS. 2:185 ; 5: 6 ; 22 :78, dan No: 138/PUU-VII/2009, sesuai QS. 2:173 ; 4 : 13,58; 5 : 3, 8, 42 ; 6 : 119.Transformasi nilai hukum Islam No. 06/PUU-II/2004, nilai keadilan, HAM, kemudahan dan humanisme. No. 27/PUU-VII/2009, nilai efektifitas, tidak memberatkan, merealisasikan manfaat, dan No. 138/PUU-VII/2009 nilai terciptanya hukum, substansi hukum, kemaslahatan, merealisasikan kemanfaatan dan keadilan. Tiga putusan yurisprudensi Mahkamah Konstitusi dikaji dari indikator THI telah mengimplemntasikan sistem norma, perilaku dan nilai. Kata Kunci: hukum integratif; Mahkamah Konstitusi; yurisprudensi.